Monday
March 27, 2017

Post a New Question

Posted by on .

solve
6x^2 - 5x +1 = 0
is this correct?

6x^2 - 2x - 3x + 1=0
-2x(-3x+1) 1(-3x +1)
(2x-1)=0 (3x-1)=0
x=1/2 x=1/3

  • MATH - ,

    The final answer is correct but there is an intermediate step that is wrong. You should have written
    (2x-1)(3x-1) = 0
    as the factoring step.

    You did break up the quadratic correctly into
    -2x(3x-1) + (-3x+ 1)
    which can be written
    (-3x+1)(-2x+1) = (3x-1)(2x-1)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question